Etnomatematika dalam Permainan Tradisional Telong-Telong - Anggraini, Dara; Risnanosanti, Risnanosanti; Masri, Masri (Jurnal Pendidikan Matematika : Judika Education, 2024)
This research aims to identify mathematical concepts contained in the traditional Telong-telong game in Bengkulu and can be used as a mathematics learning object at junior high school level. This research uses descriptive qualitative research methods and an ethnographic approach using observation, interviews and documentation. This research was conducted in the Bengkulu area, specifically the Jalan Enggano area, Pasar Bengkulu Village, Bengkulu City. This research involved one subject, namely the telong-telong maker of the Bengkulu Market group. Data analysis techniques used include data collection, data reduction, data presentation and drawing conclusions. The results of this research show that the mathematical elements contained in the traditional telong-telong game are geometric transformations, dilation, comparison and measurement. The mathematical concepts in the traditional game telong-telong can be used as objects of mathematics learning at the junior high school level. The discovery of this mathematical concept can be expanded into teaching materials such as modules, LKPD based on the traditional game Telong-telong and so on. Keywords: Ethnomathematics, Elements of Mathematics, Telong-telong.